(untitled) (Al-Qamar, 2022)
The Article lessons pragmatic study of the Qur’anic concept of Hoop. It discusses that thoughts and conducts which precise the state of hoop and they conceive the idea of nurturing faith in veins of mankind and this is causes the concept of divinity, and divinity to be refined in man, in solitude. The concept of obligation materializes when the love of Allah almighty prevails and acknowledges. Self-deception becomes a means of protection and self-accountability. The goals fulfill the Shariah and manifestations and effects of hoop and revealed the facts by which humanity in general and the Muslims in particular, by practicing, can achieve their worldly and otherworldly and eternal success and salvation.